2020
DOI: 10.3390/jcm9123828
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Mortality in Patients with Interstitial Lung Disease-Associated Pulmonary Hypertension

Abstract: Background: Pulmonary hypertension (PH) is a well-established complication in interstitial lung disease (ILD) patients. The aim of this study is to investigate the physiological and hemodynamic parameters that predict mortality in patients with ILD-PH. Methods: Consecutive ILD patients who underwent right heart catheterization (n = 340) were included. The information analyzed included demographics and physiological and hemodynamic parameters. Cox regression models were used to identify independent predictors o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 49 publications
1
28
0
Order By: Relevance
“…The recognition of PH in the course of interstitial lung disease (ILD) is burdened with a poor prognosis [17]. Negative prognostic factors in PH-ILD were identified as TLCO < 35%, 6MWT desaturation < 88%, and PVR > 4.5 WU [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recognition of PH in the course of interstitial lung disease (ILD) is burdened with a poor prognosis [17]. Negative prognostic factors in PH-ILD were identified as TLCO < 35%, 6MWT desaturation < 88%, and PVR > 4.5 WU [17].…”
Section: Discussionmentioning
confidence: 99%
“…The recognition of PH in the course of interstitial lung disease (ILD) is burdened with a poor prognosis [17]. Negative prognostic factors in PH-ILD were identified as TLCO < 35%, 6MWT desaturation < 88%, and PVR > 4.5 WU [17]. The worst outcome is observed in IPF patients, but PH in the course of CTD with UIP-like lung involvement carries a comparably poor prognosis [10,17].…”
Section: Discussionmentioning
confidence: 99%
“…As such, our findings are consistent with other racial cohorts, and importantly, we have identified additional variables highlighting the importance of parameters obtained from the 6MWT and RHC as prognostic markers in ILD patients. [ 43 ]…”
Section: Discussionmentioning
confidence: 99%
“…23 A study of 340 ILD patients undergoing RHC showed 96 (28%) of patients with PH, of which 56 were considered to be severe. 24 In a study of 135 patients with IPF being evaluated for lung transplantation, 39 patients (29%) had PH-ILD. 25 Evaluation of 488 IPF patients with mild or moderate restrictive disease showed that 14% of subjects met the criteria for PH-ILD.…”
Section: Clinical Impactmentioning
confidence: 99%
“…33 Findings similar to those in IPF have been reproduced in more general ILD population with reduced 6MWD and survival noted in patients with PH-ILD. 24,34 The severity of PH in the context of ILD is believed to generally be biased toward mild to moderate elevations in pulmonary arterial pressures. 3 In addition to fundamental pathophysiologic differences, other explanations for this include classification bias (patients with severe PH are classified as group 1) and survivorship bias (patients with advanced PH and ILD do not survive or are transplanted).…”
Section: Clinical Impactmentioning
confidence: 99%